John Chrysostom on Paul praises and problem passages - Mitchell, Margaret Mary 1956- (Atlanta, GA SBL Press, 2022)
In this new volume in the Writings from the Greco-Roman World series, Margaret M. Mitchell collects twenty-five of John Chrysostom's lesser-known sermons on Pauline passages as well as some that focus on Paul himself. Mitchell presents the Greek text and an original translation of each of these fascinating sermons in a fresh, engaging style that seeks to recapture the vibrancy and dynamism of the live oratory behind the homilies. Extensive notes to each homily evaluate how Chrysostom dealt with some of the ethical, theological, historical, political, and literary problems present in Paul's writings. Mitchell's work on Chrysostom offers a model for scholars to explore and understand how ancient Christian interpreters found in Paul's letters a legacy that was as problematic as it was precious
Includes bibliographical references (pages 817-835) and index
Text in English and Greek
Keywords: John Chrysostom -- Saint -- -407; John Chrysostom -- Saint -- -407 -- Criticism and interpretation; John Chrysostom - Saint - -407; Bible -- Sermons; Bible; Criticism, interpretation, etc; Sermons